KORESPONDENSI DAN PENATAAN ARSIP DI MTS NURUL HIKMAH CIKIWUL - Ronald Febrian; Imron Sadewa; Nurul Aulia (Program Studi Manajemen Pendidikan Islam, 2023)
Administrative management includes starting from creating, managing, structuring to storing all information materials needed by the organization. Control Archives with Schedules Create, maintain and provide services to parties in need based on file archival interests, then select the files you want to destroy or save. or in other words, all work or activities related to archive management are called archive management. This research focuses on the role of school administration in managing Madrasah school records. The purpose of this study is to find out how administrators manage records. This type of research is descriptive qualitative, namely a research procedure that produces descriptive data in the form of written or spoken language of people, and actors being observed, from the context of the individual as a whole, not in individual isolation and that is organized into variables, but consider it part of the requirements. Various techniques are used in data collection techniques in this research, namely interviews, observations and recording. The data analysis procedure used in this research is qualitative analysis. Based on the findings and discussion, the results of this research can be concluded that the role of governance in the school's efforts to manage school archives at the Private Madrasah Tsanawiyah Guppi Bintang Bayu Serdang Bedagai is carried out by storing all archives in archive storage cabinets. Archive management constraints are incomplete archive storage and irregular preparation of documents